Antibacterial Activity Test Of Leaves Bidara (Ziziphus mauritiana Lam) Ethanolic Extracts Against Staphylococcus aureus (JURNAL PROTEKSI KESEHATAN, 2021)
Infection is the most common ilnness in public. One of the triggers of infection is bacteria. Bidara leaf (Ziziphus mauritiana L) is a plant that has antibacterial compounds is phenolics, saponins and triterpenoids/steroids. The study aims to test antibacterial potency Staphylococcus. antibacterial activity testing was carried out using paper disc difussion methode, the etanol extract show antibacterial activity against Staphylococcus Aureus which is characterized by the presence of clear zone on the media. The results of ethanol extract of bidara leaves with concentrations of 30%, 50% and 70% against Staphylococcus aureus bacteria, the average diameter of inhibitory zones respectively were 8,39 mm, 10,64 mm and 12 mm with the positive control diameter of inhibition zone was 23,46 mm, the negative control diameter of inhibition zone was 0 mm.